Kemampuan Manajerial Kepala Sekolah dalam Meningkatkan Kinerja Guru di Sekolah Dasar Negeri 41 Plus Banyuasin : The Principal's Managerial Ability in Improving Teacher Performance at Public Elementary School 41 Plus Banyuasin - Lasmi Lasmi; Bukman Lian; Syaiful Eddy (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze the principal's managerial ability in improving teacher performance at State Elementary School 41 Plus Banyuasin; the principal's managerial ability is one of the important factors that influence the quality of learning because it includes planning, organizing, implementing, and supervising in school management; the research method used is descriptive qualitative with data collection techniques through in-depth interviews with 10 teachers, observation of learning activities, and documentation of school programs; the results of the study show that the principal has good managerial ability, indicated by an average score of 82% in the planning aspect, 85% in organizing, 80% in implementing, and 88% in supervising; the increase in teacher performance is reflected in the level of discipline that reaches 90%, an increase in creativity in the use of learning media by 78%, and student learning outcomes that increase by an average of 12% compared to the previous year; these findings confirm that the principal's practical managerial ability is able to encourage teachers to be more professional, increase work motivation, and create a conducive school climate; The practical implications of this research are the need to strengthen managerial training programs for school principals and support policies oriented towards improving the quality of educational leadership at the elementary school level; this research also provides an academic contribution as a basis for further studies related to the relationship between leadership management and educational quality.